Antecedents and consequences of transfer of training in public sector organizations - Icuk Rangga Bawono; Ratno Purnomo (Journal of Economics, Business, and Accountancy Ventura, 2016)
Previous studies only focused on antecedent factors of transfer of training and only a few of them focused on the consequence factors. The main objectives of this research were to examine the antecedents and consequence of transfer of training. The antecedent factors consist of individual characteristics, training design, and organizational environment. The consequence factor is individual performance. Since the previous studies used transfer of training as unidimensional construct, this research used multidimensional construct consist of knowledge sharing, training retention and training generalization. Survey with questionnaire is used as design research method. The respondents are employee who worked in state-owned hospitals (N=202). Multiple regressions was used to examine the hypothesis. The result showed that individual performance was determined by training transfer consists of three factors such as knowledge sharing, training retention, and training generalization. Training of transfer itself was determined by some factors such as individual characteristics (i.e. self-efficacy and learning orientation), training design (trainer and training material), and organizational environment (organizational support, supervisor support and peer support). Specific for organizational support, it’s only had significant effect on training retention but not on knowledge sharing and training generalization. Since transfer of training has important effect on individual performance, organization must consider the three antecedent factors.